2015
DOI: 10.1080/15257770.2015.1034363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Comparative Study of Anti-Adenoviral Activity of 6-Azacytidine and Its Analogues

Abstract: This paper presents the results of synthesis and study of cytotoxicity and the anti-adenoviral activity of new N4-derivatives of 6-azacytidine and its α-L-glycopyranosyl analogues obtained by the simplified one-pot version of the silyl condensation method. The resulting acylated 4-methylmercapto-1,2,4-triazin-3(2Н)-one glycosides then underwent the amination and/or ammonolysis to provide 6-azacytidine glycoside analogues (2-6, 12, 15, 17) and compounds with modifications at both base and sugar fragments (11, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Experimental studies have shown that azacitidine is a potent, broadspectrum antiviral agent. The range of viruses against which it shows activity includes AdV (Alexeeva et al, 2001(Alexeeva et al, , 2015, human metapneumovirus (HMPV) (Bösl et al, 2019), HIV-1 (Dapp et al, 2009;Rawson et al, 2016a), HIV-2 (Beach et al, 2014), Rift Valley fever virus (RVFV) (Ianevski et al, 2018, human T-lymphotropic virus (HTLV-1) (Diamantopoulos et al, 2012), HSV-1, and FLUAV (Ianevski et al, 2018). A study of azacytidine activity against HIV-1 and HIV-2 revealed that it primarily targets reverse transcription (in the form of 5azacytidine-triphosphate or 5-aza-2′-deoxycytidine triphosphate).…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies have shown that azacitidine is a potent, broadspectrum antiviral agent. The range of viruses against which it shows activity includes AdV (Alexeeva et al, 2001(Alexeeva et al, , 2015, human metapneumovirus (HMPV) (Bösl et al, 2019), HIV-1 (Dapp et al, 2009;Rawson et al, 2016a), HIV-2 (Beach et al, 2014), Rift Valley fever virus (RVFV) (Ianevski et al, 2018, human T-lymphotropic virus (HTLV-1) (Diamantopoulos et al, 2012), HSV-1, and FLUAV (Ianevski et al, 2018). A study of azacytidine activity against HIV-1 and HIV-2 revealed that it primarily targets reverse transcription (in the form of 5azacytidine-triphosphate or 5-aza-2′-deoxycytidine triphosphate).…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
“…The synergism was explained by the reduced accumulation of reverse transcription products rather than increased viral mutagenesis (Rawson et al, 2016b). A recent study on human adenoviruses revealed that azacytidine itself was an effective antiviral agent over a wide range of concentrations but its derivatives showed even better results, namely, N 4 -methyl-6-azacytidine and N 4 ,O-tetraacetyl-6-azacytidine, for which high selectivity against AdV and low cytotoxicity were observed (Alexeeva et al, 2015).…”
Section: Nucleoside Antimetabolites -Approved Antineoplastic Drugs Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, a number of other compounds and agents have been shown to have anti-HAdV activity in cell culture. These include cardiotonic steroids (Grosso et al, 2017), 3-hydroxy-quinazoline-2,4(1 H ,3 H )-diones (Kang et al, 2016), phenols in black tea extract (Karimi et al, 2016), dioscin, a compound extracted from air potato (Liu et al, 2013), 6-azacytidine (Alexeeva et al, 2015), and pyrrole and pyrrolopyrimidine compounds (Hamdy and El-Senousy, 2013; Mohamed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Modified nucleobases have provided interesting progress in pharmaceutical applications . For example, 5‐azacytidine and 6‐azacytidine exhibit strong activity by means of their triazine skeletons (Figure ) . Modulation of the sugar part has also found many applications in the pharmaceutical field.…”
Section: Introductionmentioning
confidence: 99%